Residuality and Inconsistency in the Interpretation of Socio-Theoretical Systems. (September 2019) - Bouzanis, Christoforos; Kemp, Stephen
This article addresses the interpretation and criticism of theoretical systems. Its particular focus is on how to assess the success of theories in dealing with some specific phenomenon. We are interested in how to differentiate between cases where a theory offers an unsatisfactory acknowledgment of a specified phenomenon and those where a theory offers a deeper, more systematic understanding. We address these metatheoretical issues by developing Parsons's analysis of positive and residual categories in various respects, including a focus on mutual support as the basis of positivity, differentiating synectic (reconcilable) and antinomic (irreconcilable) residual categories, and distinguishing divisions that are central to systems from those between center and periphery. We also consider how this conceptual toolkit can be put into practice.